PERLINDUNGAN HUKUM TERHADAP PEMENANG LELANG ATAS OBJEK YANG DIBELI MELALUI LELANG (STUDI PUTUSAN PENGADILAN NEGERI NOMOR: 121/PDT.G/2014/PN.MDN) - SONDANG SIMANJUNTAK (PREMISE LAW JURNAL, 2017)
Collateral is legal protection for creditor when debtor cannot take his responsibility to pay off his debt to the creditor. The pay off to the creditor is by selling the collateral through public auction. The problem in auction occurs when the winner does not have the collateral he has bought since it is difficult to get it and there is complaint from the debtor. the process of the auction will cause the collateral is shifted from the seller to the winner of the auction, but it brings about a problem such as the winner cannot own the auction object. In this research, the implementation of auction has been ion accordance to the Decree of the Minister of Finance No. 93/PMK/06/2010 on the Operational Manual, the responsibility of the auctioneer, and the Bank in withdrawing the collateral auctioned is not involved so that the auction buyer/winner does by himself in withdrawing the auction object or the winner submit a request for execution to the District Court where the object is placed. Legal protection should be given to the auction winner in order to create legal certainty for the auction winner on the auction object he has bought. The conclusion is that an auction winner who has good faith (intention) has not yet obtained legal protection so far. Keywords: Legal Protection, Auction Winner, Auction Object